CHOLESTASIS IN ACUTE AND CHRONIC VIRAL HEPATITIS - V. F. Uchaikin; O. V. Molochkova; A. G. Pisarev; T. V. Cherednychenko; G. V. Chaplygina (LLC "Diagnostics and Vaccines", 2015)
We observed 43 patients with cholestasis (21 - with acute viral hepatitis A and B and 22 - with chronic viral hepatitis B and C). Etiological diagnosis was based on the identification of specific markers of the spectrum. These 43 patients in addition to basic therapy ursodeoxycholic acid as a drug Ursosan of company «PRO.MED.CS Praha a.s.» (CzechRepublic). The control group consisted of 17 patients with acute viral hepatitis. Clinical signs are jaundice and itching of the skin, abdominal pain, significant hepatomegaly. Serum bilirubin level rises due to the conjugated fraction, alkaline phosphatase, gamma-glutamyltranspeptidase. When ultrasound revealed dilated bile ducts in the liver parenchyma, reactive edema of the gallbladder wall, signs gipomotornoy dyskinesia. Appointment ursosan in acute and chronic viral hepatitis occurring with cholestasis leads to the clinical and biochemical effects, and has a beneficial effect on the state of the liver and gall bladder.